ANALISIS FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP ABNORMAL RETURN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Ema Lisa Hs Ningrum, 12.05.52.0055; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2016)
Abnormal return is the difference between the actual return with the expected return. Investors expect a normal return corresponding capital invested but investors get the return exceeds the expected return. The study examine the effect of company growth, capital structure, earnings, and company size on abnormal return. Population in this research is manufacturing company listed on the Indonesian Stock Exchange period 2011 to 2014. The sampling method used purposive sampling. Based on the criteria then obtained a sample of 316 companies. Hypothesis testing using multiple regression analysis. The result showed that the company growth and capital structure has no significant positive effect and earnings has significant positive effect to the abnormal return. Where as the company size has significant negative effect to the abnormal return.Keywords: Company Growth, Capital Structure, Earnings, Company Size, Abnormal Return